Strength of Soft Clay Reinforced with Single and Group Bottom Ash Columns - Muzamir, Hasan; Aminaton, Marto; Hyodo, Masayuki (2014)
Stone column could be implemented as a ground improvement technique where a portion of the soil is substituted with granular material such as sand or crushed rocks which is proven to improve bearing capacity and accelerate the dissipation of pore water pressure. This research was aimed to investigate the role of bottom ash columns in improving the shear strength soft reconstituted kaolin clay. This was done by determining the effect of area replacement ratio, height penetrating ratio and volume replacement ratio of a single bottom ash columns on the strength of kaolin clay reinforced with bottom ash column(s). The reinforced kaolin samples were tested using Unconfined Compression Test (UCT). Research variables include diameter and height of the bottom ash columns. Through the results of UCT, it can be concluded that the S u generally increased with the increased in the height penetrating ratio but decreased after reaching an optimum improvement at 80 % of height penetrating ratio. The increment of Su was also dependent on the area replacement ratio of bottom ash. However, excessive area replacement decreased the shear strength of the sample reinforced by group columns since the remaining width of the soil sample will be too thin to hold the columns. Generally it can be concluded that the shear strength of soft clay could be improved by the installation of bottom ash columns.